Two new species of Austrolimnius Carter & Zeck (Insecta: Coleoptera: Elmidae) from Southeastern Brazil - de Miranda, Gustavo Silva; Sampaio, Brunno Henrique Lanzellotti; Da Silva Dos Passos, Maria Inês (Zootaxa, 2012)
The genus Austrolimnius Carter & Zeck has its greatest known diversity in Oceania, but its fauna in the Americas is poorlyknown. In this paper, two new species—Austrolimnius uncatus sp. nov. and A. bocainensis sp. nov.—are described and illus-trated based on adult specimens collected at Serra da Bocaina National Park, São José do Barreiro Municipality, São PauloState, and Nova Friburgo Municipality, Rio de Janeiro State, Brazil. Austrolimnius uncatus sp. nov. is characterized by the longsetae on the mesotarsus, the medial expansion of the hind tibiae, and the hook-like shape of the male genitalia. Austrolimniusbocainensis sp. nov. can be recognized by the absence of setae on the mid-tarsus, the cylindrical hind tibiae, and the slightlycurved genitalia with few setae. A pictorial key for the Brazilian species of the genus is given. New records of Brazilian species of the genus are reported.